Implantable photonic neural probes with 3D-printed microfluidics and applications to uncaging - Xin Mu; Xin Mu; Fu-Der Chen; Fu-Der Chen; Fu-Der Chen; Ka My Dang; Ka My Dang; Michael G. K. Brunk; Michael G. K. Brunk; Jianfeng Li; Jianfeng Li; Hannes Wahn; et al. (Frontiers in Neuroscience, 2023)
Advances in chip-scale photonic-electronic integration are enabling a new generation of foundry-manufacturable implantable silicon neural probes incorporating nanophotonic waveguides and microelectrodes for optogenetic stimulation and electrophysiological recording in neuroscience research. Further extending neural probe functionalities with integrated microfluidics is a direct approach to achieve neurochemical injection and sampling capabilities. In this work, we use two-photon polymerization 3D printing to integrate microfluidic channels onto photonic neural probes, which include silicon nitride nanophotonic waveguides and grating emitters. The customizability of 3D printing enables a unique geometry of microfluidics that conforms to the shape of each neural probe, enabling integration of microfluidics with a variety of existing neural probes while avoiding the complexities of monolithic microfluidics integration. We demonstrate the photonic and fluidic functionalities of the neural probes via fluorescein injection in agarose gel and photoloysis of caged fluorescein in solution and in fixed brain tissue.